Therapeutic enquiries about biological agents as a tool to identify safety aspects and patterns of use. Issue 3 (28th October 2015) - Salat, D; Llop, R; Aguilera, C; Danés, I; Bosch, M; Asensio, C; Castañeda, F; Esterlich, E; Vallano, A
Abstract : Background: Biotechnological agents (BA) are increasingly being used in clinical practice. We aimed to determine, whether enquiries about them to a therapeutic consultation service have also become more frequent, and to describe the information requested in these consultations. Methods: We retrospectively reviewed 14 104 therapeutic consultations collected in a computerised database between 2000 and 2014. Enquiries about BA (monoclonal antibodies, fusion proteins or cytokine antagonists) were chosen. Information on the type of BA, underlying condition, type of enquiry and affiliation of the enquirer was retrieved and compared with data from consultations about other agents. Results: During the study period, 365 enquiries about 30 different BA were received. Only 4% of them were received before 2004, while 48.8% were received after 2010. Rituximab, infliximab, adalimumab and etanercept were most frequently enquired about. Agent selection (n=184) and/or adverse effects (n=174) were the most frequent reasons for making an enquiry. Most enquiries about an agent selection were made about an off-label use (n=164), mainly for systemic autoimmune diseases (n=61). Over half of the enquiries about adverse effects were about their teratogenic potential (n=96). Enquiries about BA more often requested an opinion (87.7% vs 77.7%) were made by physicians (89.9% vs 76.9%), from a hospital (81.6% vs 44.5%) and regarded a specific patient (87.4% vs 74.5%). Conclusions: Therapeutic consultations about BA are increasing. Most of them are related to uncertainties of health professionals regarding any new medicine: their off-label use, actual adverse effects or the teratogenic potential of the involved agents.